Cristulariella moricola associated with foliar blight of Camden white gum (Eucalyptus benthamii), a bioenergy crop. (October 2017) - Aubrey, Doug P.; Fraedrich, Stephen W.; Harrington, Thomas C.; Olatinwo, Rabiu
Abstract: We report the association of Cristulariella moricola (Hino) Redhead with a zonate leaf spot on Eucalyptus benthamii (Myrtaceae). We observed the disease outbreak across a series of experimental E. benthamii plantings in Barnwell County, South Carolina, USA in October 2015. The disease caused nearly complete foliar necrosis of most trees in one experimental planting, but disease incidence remained at low levels (<10% of foliage affected in most trees) in other plantings. Disease development coincided with periods of extended rainfall, which has also been observed in outbreaks of zonate leaf spot caused by C. moricola in other tree species. Highlights: Zonate leaf spot and subsequent blight occurred on Eucalyptus benthamii . Zonate leaf spot and subsequent blight were associated with Cristulariella moricola . Disease outbreak occurred in South Carolina, USA. Disease caused nearly complete foliar necrosis. Disease development coincided with periods of extended rainfall.